2018
DOI: 10.1021/acsami.7b16524
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Viruslike and Charge Reversible Nanoparticles to Sequentially Overcome Mucus and Epithelial Barriers for Oral Insulin Delivery

Abstract: Nanoparticles (NPs) for oral delivery of peptide/protein drugs are largely limited due to the coexistence of intestinal mucus and epithelial barriers. Sequentially overcoming these two barriers is intractable for a single nanovehicle due to the requirements of different or even contradictory surface properties of NPs. To solve this dilemma, a mucus-penetrating virus-inspired biomimetic NP with charge reversal ability (P-R8-Pho NPs) was developed by densely coating poly(lactic- co-glycolic acid) NPs with cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 40 publications
4
76
1
Order By: Relevance
“…For overcoming the barriers of mucus, mucus-adhesive NPs (MAPs) and mucus-penetrating NPs (MPPs) have been developed, and results have revealed that MPPs diffused more freely than MAPs, exhibiting improved distribution and access to the absorptive epithelium203, 204. In addition, shape and elasticity are also reported to affect mucus diffusion205, 206.…”
Section: Peptide and Protein Drug Deliverymentioning
confidence: 99%
“…For overcoming the barriers of mucus, mucus-adhesive NPs (MAPs) and mucus-penetrating NPs (MPPs) have been developed, and results have revealed that MPPs diffused more freely than MAPs, exhibiting improved distribution and access to the absorptive epithelium203, 204. In addition, shape and elasticity are also reported to affect mucus diffusion205, 206.…”
Section: Peptide and Protein Drug Deliverymentioning
confidence: 99%
“…This is the case of the EGP peptide‐functionalized PLGA nanoparticles,50 targeting heparan sulfate proteoglycans (HSPGs). The same strategy was adopted51 to decorate PLGA NPs with octa‐arginine (R8) peptide linked to phosphoserine (PhO). In theory, the brush border intestinal alkaline phosphatase (IAP) would catalyze the hydrolysis of PhO from the nanoparticles surface, hence exposing the cationic R8 residues, which would promote cell uptake.…”
Section: Recent Advances In Preclinical Stage On Systemic Delivery Ofmentioning
confidence: 99%
“…To confirm the maintained biological activity of insulin after encapsulated into IPC-NEs, the hypoglycemic effects of the released insulin were evaluated in normal rats according to a previous report 23. After subcutaneous injection, the released insulin from IPC-NEs and IPC showed similar hypoglycemic profiles as compared to the equivalent dose of free insulin (1 IU/kg; Figure 6A).…”
Section: Resultsmentioning
confidence: 88%
“…To imitate the GT environment, we conducted in vitro release study in SGF for the first 2 hrs and in SIF for another 6 hrs, without enzymes 23. As illustrated in Figure 4A, both of free insulin and IPC had a fast release profile, with more than 80% of the insulin were released within the first 2 hrs.…”
Section: Resultsmentioning
confidence: 99%